The Factors Contributed of incidence phlebitis cases with patients by using cannula in National Hospital Guido Valadares Dili, Timor Leste - Joaquim Pinto; Fulgensio Cristin Gusmão; Ostelino da Silva Belo; Chusnatayaini, Arina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Phlebitis is defined as inflammation of the vein wall where 2 complications that may develop as a result of phlebitis are: infection resulting from an accumulation of neutrophils; and thrombus, which may lead to complete occlusion of the vein. As healthcare professionals cannot look inside veins during IV therapy, they must rely on what they can see, feel and ask, i.e. detectable changes in skin color, texture, temperature and sensitivity, to identify the development of phlebitis. The absence of a good blood flow and the presence of a poor infusion rate have also been cited as clinical indicators of phlebitis Observation of the patient for clinical signs and symptoms of phlebitis is therefore the key to preventing serious venous damage. Health professional hands are a common of spreading microorganisms, thus very important for health workers followed one of precaution is to attention wash your hands of properly. Phlebitis is caused by chemical factors (type of net liquids), mechanical factors (insertion measures in place), and the most common factors (hand washing techniques including the factors of the patient's age), have been caused by phlebitis. The same results in some research conducted by some researchers show that the causes of phlebitis, among them, the types of liquidity and knowledge of nurses, type of therapy, and development of children, the location and the application of these measures were not yet put in place. The design of research is a quantitative study, with a cross-sectional approach. The sampling technique in this study was accicental sampling, with a sample of 56 respondents. The study was conducted on November 2022 in National Hospital Guido Valaradres Dili, Timor Lest. The result of study showed that the cannula factor influence the phlebitis of the correlations is 0.605 and significant P value is 0.000, time/duration using cannula factor influence the phlebitis of the results correlations is 0.633 and significant P value is 0.000 and the age factor influence the phlebitis of the correlations = 0.736 and significant P value is 0.000